European Mobility Week – A Factor for the Development of Sustainable Urban Mobility - Dimitrova, Alexandra (Research Papers, 2025)
This report examines the essence of the “European Mobility Week” initiative both for the countries of the European union and for our country Bulgaria. The main goal for the development of the text is the promotion of the ecological way of moving people and the achievement of sustainable urban mobility in the small and large settlements through the implementation of mobile activities that will help to solve several problems related to the environment in today’s 21st century.